La ansiedad lingüística en la comunicación oral en inglés en estudiantes de primer nivel de la Universidad Nacional de la Amazonía Peruana de Iquitos 2023 - Cardenas Guerra, Mabel (2024)
The general objective of the study was to determine the influence of linguistic anxiety on oral communication in English in first level students of the Universidad Nacional de la Amazonia Peruana Iquitos 2023. This study was an explanatory study with field, cross-sectional and multivariate designs. The study population consisted of 1829 individuals, with a sample of 318 students. Data collection tools included a linguistic anxiety questionnaire, an oral comprehension test, and an oral production test, all of which were validated and reliable. Consequently, the findings indicated a linear correlation between linguistic anxiety and oral communication. In conclusion, the linear regression test confirmed that there is influence between the two variables, as the B value was 0.60 with a p-value of 0.000, which is less than 0.05.